2019
DOI: 10.1136/bmjgh-2019-001871
|View full text |Cite
|
Sign up to set email alerts
|

After the Astana declaration: is comprehensive primary health care set for success this time?

Abstract: Primary health care (PHC) strengthening in order to achieve the Sustainable Development Goal has again, 40 years after the Alma-Ata declaration, been declared a priority by the global health community. Despite initial progress the Alma-Ata vision of Health for All by the year 2000 was not realised. In this analysis we (1) examine the challenges that comprehensive PHC faced after the Alma-Ata declaration, (2) provide an analysis of the current opportunities and threats to comprehensive PHC strengthening on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 53 publications
0
36
0
Order By: Relevance
“…Following the Astana Declaration in 2018, 11 , 12 there is increased interest from countries to transform their primary health-care systems towards UHC. 13 However, the aspiration to UHC will be realized only if there is a political commitment that will be translated into three interrelated and synergistic pillars of primary health care: (i) universal access to quality health services (supported by essential public health functions) and equity of access to health care; (ii) empowered people and communities; and (iii) multisectoral policy and action for health.…”
Section: Introductionmentioning
confidence: 99%
“…Following the Astana Declaration in 2018, 11 , 12 there is increased interest from countries to transform their primary health-care systems towards UHC. 13 However, the aspiration to UHC will be realized only if there is a political commitment that will be translated into three interrelated and synergistic pillars of primary health care: (i) universal access to quality health services (supported by essential public health functions) and equity of access to health care; (ii) empowered people and communities; and (iii) multisectoral policy and action for health.…”
Section: Introductionmentioning
confidence: 99%
“…27 Primary healthcare strengthening has been made a priority health development objective again in various forums including the Astana conference in 2018. 28 This development provides opportunities for additional political attention, a push for additional scientific evidence and economic resources from official development assistance and other donors.…”
Section: Eancda Policy Recommendations Based On the Benchmark Surveymentioning
confidence: 99%
“…The most cost-efficient way to ensure access to both health care for communicable and non-communicable disease are horizontally integrated primary health care systems that involve the community (eg, community health workers). 16 In particular the third pillar of the strategy to ensure population health, promoting health and well-being, touches upon NCDs as those can only be controlled in a sustainable manner by employing primordial, primary and secondary prevention strategies. Due to its holistic nature, community-focus, and core values, PHC aligns well with the needs of the NCD epidemic, reflecting the challenges of chronic conditions that require long-term treatment and community-based prevention.…”
mentioning
confidence: 99%
“…20 Furthermore, a wealth of experience and evidence for improving PHC financing, governance and implementation exists that can facilitate PHC strengthening in low- and middle-income countries. 16 , 21 Despite these developments, primary health care structures, as well as tertiary level critical and specialized care, are still inadequate and inefficient in large parts of Sub-Saharan Africa. 15 A recent study found that across this region close to 30% of people cannot access emergency care within two hours of travel time.…”
mentioning
confidence: 99%